Mitochondrial genome of Quercus chenii: genomic features and evolutionary implications - Xuan Li; Shixin Zhang; Yongfu Li; Yousry A. El-Kassaby; Yanming Fang (BMC Genomics)
Abstract Recent advances in high-throughput sequencing have enabled detailed characterization of plant mitochondrial genomes. Here, we assembled and analyzed the mitochondrial genome of Quercus chenii Nakai, a key oak species in Fagaceae, using Illumina NovaSeq6000. The genome consists of a 364,958 bp linear and a 53,677 bp circular chromosome, totaling 418,635 bp with a GC content of 45.6%. Repeat-rich regions (210–250 and 300–340 kb) may facilitate structural rearrangements, while extensive RNA editing-particularly in nad4 and ccmF-likely enhances protein functionality and mitochondrial adaptability. Comparative collinearity analysis showed high structural conservation with Q. acutissima Carruth. (90.92%) but marked divergence from Fagus sylvatica L. (35.80%), suggesting lineage-specific rearrangements. Phylogenetic analysis based on the mitochondrial genome supports the same placement of Q. chenii within Fagaceae as that derived from the chloroplast genome. The Ka/Ks analysis across Fagaceae mitochondrial genomes revealed strong conservation of core genes, with adaptive variations in energy metabolism-related genes, suggesting functional divergence linked to metabolic optimization under environmental stress. These findings highlight the distinct evolutionary strategies of mitochondrial and chloroplast genomes: the former optimizing energy production, while the latter fine-tunes photosynthesis and stress responses. Comparison analysis with the chloroplast genome further revealed both conserved (psbT and psbC) and divergent (ndhD and ndhF) genes, implying potential historical gene transfer events. Together, these findings highlight the dynamic yet conserved nature of the Q. chenii mitochondrial genome and provide new insights into organellar genome evolution, structural plasticity, and adaptive mechanisms within the Fagaceae family.